High Prevalence of Antinuclear Antibodies in Children with Thyroid Autoimmunity - Maria Segni; Ida Pucarelli; Simona Truglia; Ilaria Turriziani; Chiara Serafinelli; Fabrizio Conti (Journal of Immunology Research)
Background. Antinuclear antibodies (ANA) are a hallmark of many autoimmune diseases and can be detected many years before disease onset. Autoimmune thyroid diseases (AITD) are frequently associated with other organ- and non-organ-specific autoimmune disorders. Objectives. To assess the prevalence of ANA in pediatric patients with AITD and their clinical correlations. Methods. Ninety-three consecutive pediatric patients with AITD were enrolled (86 children with chronic lymphocytic thyroiditis and 7 with Graves’ disease). ANA, anti-double DNA (anti-dsDNA) antibodies, anti-extractable nuclear antigen (anti-ENA), anti-cyclic citrullinated peptide antibodies (anti-CCP), and rheumatoid factor (RF) was obtained. Signs and symptoms potentially related to rheumatic diseases in children were investigated by a questionnaire. Results. ANA positivity was found in 66/93 children (71%), anti-ENA in 4/93 (4.3%), anti-dsDNA in 1/93 (1.1%), RF in 3/93 (3.2%), and anti-CCP in none. No significant differences were found between the ANA-positive and ANA-negative groups with respect to age, sex, L-thyroxine treatment, or prevalence of other autoimmune diseases. Overall, parental autoimmunity was found in 23%. Conclusions. ANA positivity was demonstrated in 71% of children with AITD. ANA positivity was not related to overt immune-rheumatic diseases. However, because the positivity of ANA can occur even many years before the onset of systemic autoimmune diseases, prospective studies are warranted.